If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X(a + -4b) = 5m(x + -1c) * forx (a * X + -4b * X) = 5m(x + -1c) * forx (aX + -4bX) = 5m(x + -1c) * forx Reorder the terms: aX + -4bX = 5m(-1c + x) * forx Reorder the terms for easier multiplication: aX + -4bX = 5m * forx(-1c + x) Multiply m * forx aX + -4bX = 5fmorx(-1c + x) aX + -4bX = (-1c * 5fmorx + x * 5fmorx) aX + -4bX = (-5cfmorx + 5fmorx2) Solving aX + -4bX = -5cfmorx + 5fmorx2 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '4bX' to each side of the equation. aX + -4bX + 4bX = -5cfmorx + 4bX + 5fmorx2 Combine like terms: -4bX + 4bX = 0 aX + 0 = -5cfmorx + 4bX + 5fmorx2 aX = -5cfmorx + 4bX + 5fmorx2 Reorder the terms: aX = 4bX + -5cfmorx + 5fmorx2 Divide each side by 'X'. a = 4b + -5cfmorxX-1 + 5fmorx2X-1 Simplifying a = 4b + -5cfmorxX-1 + 5fmorx2X-1
| 1/4=x-2/9 | | 10x-5=9-6x | | C=2*3.14*3 | | 130+4x=234-2.5x | | a-3b=43 | | y-4(2-y)+3y=3(y-4) | | X(a-4b)=5m(x-c) | | 9.375=X/4 | | 3p=4/5 | | (-4x^6d^3)(6x^3d)= | | 6.5x=104 | | n=(n+8)/3 | | 13(x+2)(x+2)-5=22 | | x*2/3+6=-3 | | 16(z-1)(z-1)-29=-28 | | lx+2l=3x | | x*1=1 | | 9(z+1)(z+1)+12=16 | | x=-5+3y | | 7x-4=-46 | | (y+3)(y+3)=4 | | p+26=22 | | -2/3a=6 | | 12(x-11)(x-11)+12=30 | | a^2+b^2-1=0 | | 9d+(8+5.5)=24 | | 81n+33=42 | | p-13=-5 | | 4(9-y)xy+4y=36 | | 9d+(8+6)=24 | | 25(z+2)(z+2)-35=-36 | | h=9 |